A Referential Interpretation al-Jaryī wa al-Inṭibāq: Approach (Tafsīr Taṭbīqī) for Digging The Inner Meaning of al-Qur'an. - Kerwanto, Kerwanto (UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Some important criteria that must be considered by the commentator in determining the inner (esoteric) meaning of the Qur'an are that it must not conflict with the literal text, mutawatir hadiths and important religious principles (dharuriyāt ad-dīn). Once the requirements that must be met in the interpretation are so strict, not a few products of isyari interpretation (Sufi interpretation) are considered deviant and trapped in tafsir bi al-ra’yī al-madzmum (despicable interpretation). Therefore, it is important to carry out several in-depth reviews of various approaches and rules of interpretation that can be used as a medium for revealing and explaining the inner meaning of the Qur'an. In this article, the author tries to clarify the important position of the rule of al-jaryī wa al-Inṭibāq in the interpretation of the Qur'an, which is very likely in some cases not paid attention to by some commentators. For the author, this rule can be a bridge in determining the validity of the inner meaning of the Qur'an because the main element of this rule is the hadiths that are related to the context of the nuzūl verse. The main working principle of this rule is to try to apply certain references intended by the verses of the Qur'an to several different individuals at different times and places with the context of the initial nuzul of the verse. This rule seeks to find new meanings from the general concept of the verse which is abstracted from hadith data that is related to the context of its nuzul.